2014
DOI: 10.1371/journal.pone.0100513
|View full text |Cite
|
Sign up to set email alerts
|

Skeletal Muscle Expression of the Adhesion-GPCR CD97: CD97 Deletion Induces an Abnormal Structure of the Sarcoplasmatic Reticulum but Does Not Impair Skeletal Muscle Function

Abstract: CD97 is a widely expressed adhesion class G-protein-coupled receptor (aGPCR). Here, we investigated the presence of CD97 in normal and malignant human skeletal muscle as well as the ultrastructural and functional consequences of CD97 deficiency in mice. In normal human skeletal muscle, CD97 was expressed at the peripheral sarcolemma of all myofibers, as revealed by immunostaining of tissue sections and surface labeling of single myocytes using flow cytometry. In muscle cross-sections, an intracellular polygona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 43 publications
0
12
0
Order By: Relevance
“…Recently, ADGRE5 (CD97) was detected not only in the sarcolemma as other Adhesion GPCRs but also in the sarcoplasmatic reticulum of myocytes. Adgre5 (Cd97)-knockout mice showed a dilated sarcoplasmatic reticulum; yet, despite this severe ultrastructural alteration, the mice had no overt skeletal muscle phenotype (Zyryanova et al, 2014), which is similar to as Adgrb1 (Bai1)-and Adgrg1 (Gpr56)-deficient mice (Hochreiter-Hufford et al, 2013;Wu et al, 2013) and may indicate compensatory mechanisms.…”
Section: Skeletal Muscle and Bonementioning
confidence: 85%
See 2 more Smart Citations
“…Recently, ADGRE5 (CD97) was detected not only in the sarcolemma as other Adhesion GPCRs but also in the sarcoplasmatic reticulum of myocytes. Adgre5 (Cd97)-knockout mice showed a dilated sarcoplasmatic reticulum; yet, despite this severe ultrastructural alteration, the mice had no overt skeletal muscle phenotype (Zyryanova et al, 2014), which is similar to as Adgrb1 (Bai1)-and Adgrg1 (Gpr56)-deficient mice (Hochreiter-Hufford et al, 2013;Wu et al, 2013) and may indicate compensatory mechanisms.…”
Section: Skeletal Muscle and Bonementioning
confidence: 85%
“…Human ADGREs (EGF-TM7 receptors) are useful markers for granulocytes, with ADGRE1 (EMR1) found on eosinophils and ADGRE3 (EMR3) on mature polymorphogenic granulocytes Matmati et al, 2007;Legrand et al, 2014). In contrast, ADGRE5 (CD97) is not restricted to myeloid cells but also found on lymphoid, epithelial, muscle, and other cell types (Eichler et al, 1994;Jaspars et al, 2001;Aust et al, 2006;Veninga et al, 2008;Zyryanova et al, 2014).…”
Section: Expressionmentioning
confidence: 99%
See 1 more Smart Citation
“…The frequent induction, upregulation, and/or biochemical modification of CD97 in tumor cells, compared to the corresponding normal cells (Aust et al, 1997(Aust et al, , 2002(Aust et al, , 2006Steinert et al, 2002;Wobus et al, 2004;Coustan-Smith et al, 2011;Bonardi et al, 2013;Mirkowska et al, 2013;Ward et al, 2013;Zyryanova et al, 2014), suggests that this Adhesion GPCR is involved in basic cellular and molecular processes during tumorigenesis. Here, we demonstrated that CD97 overexpression inhibits intrinsic apoptosis, mediated by serum starvation or staurosporine, as well as extrinsic apoptosis, induced by TNF/CHX treatment.…”
Section: Discussionmentioning
confidence: 99%
“…In the corresponding malignant tumors, CD97 is found to be induced or upregulated (Aust et al, 1997(Aust et al, , 2002(Aust et al, , 2006Steinert et al, 2002;Wobus et al, 2004;Ward et al, 2013). In leio-and rhabdomyosarcoma, CD97 is in part N-glycosylated, whereas normal muscle cells express the "naked" CD97 protein core (Aust et al, 2006;Zyryanova et al, 2014), indicating tumor-specific post-translational modification of the receptor. Expression levels of CD97 correlate with dedifferentiation in thyroid carcinoma (Aust et al, 1997;Ward et al, 2013).…”
Section: Introductionmentioning
confidence: 99%